Incidence of hypermucoviscous Klebsiella pneumoniae and phenotypic detection of their virulence factors along with classical strains among patients visiting tertiary care hospital - Thapa, Tika Bahadur; Maharjan, Sujina; Giri, Nisha; Sapkota, Manisha; Shrestha, Ojaswee; Khanal, Puspa Raj; Joshi, Govardhan (The Journal of Infection in Developing Countries, 2025)
Introduction: A new strain of Klebsiella pneumoniae named hypermucoviscous K. pneumoniae emerges with a distinctive feature to classical strains. Infections due to hypermucoviscous strains have increased with significant mortality and morbidity. This study aimed to determine the prevalence of hypermucoviscous K. pneumoniae and compare their virulence with the classical strains phenotypically. Methodology: One hundred-five clinical isolates of K. pneumoniae isolates proceeded for the study. A modified string test evaluated the hypermucoviscosity. The determination of antibiotic susceptibility was done using the Kirby-Bauer disk diffusion method. A phenotypic combination disk test was used to detect β-lactamases (ESBL, MBL, and KPC). Serum resistance was determined by the viable count method, and biofilm production by the microtiter plate method. Results: The modified string test detected 27.6% (29/105) of isolates as hypermucoviscous and 72.4% (76/105) as classical K. pneumoniae. Most K. pneumoniae were resistant to ceftazidime (80%) and cefotaxime (78%), and 46.7% were resistant to both imipenem and meropenem. A combination disk test identified 53.3% of ESBL, 28.6% of MBL, and 17.2% of KPC producers. Furthermore, 24.8% of K. pneumoniae were biofilm producers, and 39% were found to be serum resistant. Conclusions: In comparison, classical strains were more likely to develop ESBL, MBL, KPC, and biofilms while hypermucoviscous strains have higher serum resistance. The present study revealed that hypermucoviscous K. pneumoniae strains are prevalent and can be associated with metastatic invasive infections. Therefore, appropriate treatment strategies and timely diagnosis of these strains to limit their infection are crucial.